STRATEGIES FOR IMPROVING NURSE PERFORMANCE THROUGH STRENGTHENING THE JOB CHARACTERISTICS, PERSONALITY, AND JOB SATISFACTION: A MIXED METHODS APPROACH AT COMMUNITY HEALTH CENTERS IN SOUTH TANGERANG CITY - Sunarto, Ading; Moeins, Anoesyirwan; Sunaryo, Widodo (International Journal of Multidisciplinary Research and Literature, 2025)
Nurse performance is a crucial factor in determining the quality of health services at community health centers. This study aims to develop strategies to improve nurse performance by strengthening job characteristics, personality, and satisfaction. A mixed methods approach combined a quantitative survey of 141 Puskesmas nurses in South Tangerang City and qualitative analysis through the Delphi technique with Focus Group Discussion (FGD). Quantitative analysis was performed using path analysis to test the direct and indirect effects between variables and the Sobel test to assess the mediating role of job satisfaction. The results showed that job characteristics, personality, and satisfaction directly, positively, and significantly affected nurse performance. Job characteristics and personality were also found to influence job satisfaction, while the mediating role of job satisfaction, although significant, was not stronger than the direct effect. Qualitative findings through Delphi–FGD supported the quantitative results by showing consistency between nurses' perceptions in the survey and their field experiences, thereby strengthening the validity of the findings. This study concludes that strategies to improve nurse performance in Puskesmas can be directed through three main focuses: strengthening job design, fostering upbeat personality, and increasing job satisfaction. The results of this study are expected to contribute to the development of human resource management in the health sector, while providing a practical basis for policymakers in designing interventions to improve service quality.